Prevention of man-in-the-middle attack against HTTPS website / Nur Syahirah Zainalabidin - Zainalabidin, Nur Syahirah (2020)
The Man-In-The-Middle (MITM) attack is one of the most well-known attacks on computer security, posing one of the greatest issues for security professionals. MITM addresses the actual data that flows between endpoints, and the confidentiality and privacy of the data itself. Nonetheless, secure web sites typically use HTTPS connection to secure transactions such as money transfers, online payment, and ecommerce. The use of HTTPS provides a sense of security against threats such as man in the middle (MITM) attack. The objective of this paper are to design the countermeasure against MITM in target machine and counter-measure of the MITM are proposed. Also, in this paper we have discussed about how MITM attack can attack HTTPS sites even though it is known as secure websites and we have designed the counter-measure of it using the correct tools.